AUTHENTIC ASSESSMENT IN LEARNING WRITING OF CLASS VII STUDENTS IN THE STATE OF MEMPAWAH HULU - Lisa, Desi Marianti; Saman, Sisilya; Priyadi, Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the planning and results of authentic assessment on learning to write letters of grade VII students at SMP Negeri Mempawah Hulu Landak Regency in 2019. The method used in this research is descriptive qualitative to obtain detailed and clear information so as to provide an authentic picture of reality assessment The teacher of Mempawah Hulu Middle School, especially Indonesian subjects on letter writing material official. Based on the results of this study it was found that the implementation of learning by Indonesian teachers conducted by teachers in three State Public Schools in Mempawah Hulu was in accordance with the 2013 Curriculum. Overall the average value of authentic assessment on aspects of knowledge 72.67, 70.89 skills and attitude 86 , 33 for three State Public Schools in Mempawah Hulu Landak Regency above the KKM value set by the three schools is 70 so that the level of completeness is in accordance with the implementation of 2013 curriculum learning. The results of this research are expected to be continued at the elementary and high school levels so that they can know the learning process and authentic assessment of the 2013 curriculum implementation.Keywords: Authentic Assessment, Learning to Write Letters, Junior High School Students.